Advances in electron transfer chemistry - Mariano, Patrick S. (Jai Press Inc., 1991)
Part of a series which aims to provide coverage of the chemical and biochemical aspects of electron transfer chemistry. This fourth volume discusses such topics as: intramolecular photochemical electron transfer induced bond cleavage reactions in some sulfonium salt derivatives.